If , where , , and are positive integers , then find .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Without loss of generality let x ≤ y ≤ z . The given equation can be rewritten as
2 x ( 1 + 2 y − x + 2 z − x ) = 2 3 3 6 = 2 5 ∗ 7 3 .
By the Fundamental Theorem of Arithmetic, (FTA), we can conclude that x = 5 and that
1 + 2 y − x + 2 z − x = 7 3 ⟹ 2 y − x ( 1 + 2 z − y ) = 7 2 = 2 3 ∗ 3 2 .
Again by the FTA we can conclude that y − x = 3 ⟹ y = 8 and that
1 + 2 z − y = 9 ⟹ 2 z − y = 8 = 2 3 ⟹ z − y = 3 ⟹ z = 1 1 .
Thus x + y + z = 5 + 8 + 1 1 = 2 4 .